(untitled) (Journal of Scientific Research, 2014)
Cinnamomum alexei Kosterm. has been reinstated to its original status as a distinct species from C. verum J.S. Presl, provided with a short taxonomic diagnosis. Keywords: Taxonomic note; Cinnamomum alexei; C. verum; Lauraceae, India. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17091 J. Sci. Res. 6 (2), 395-397 (2014)